Feline scabies (Notoedric Mange) in a cat: A case report - Sai Krishna Sindhuja, K; Jalajakshi, K; Varaprasad Reddy, L S S; Chandrakala, M; Venkata Sumanth Reddy, G (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A clinical case of feline scabies was recorded in an eleven month old male cat. With thick yellow crusty erythematous lesions and alopecia on the head and ears, the skin scrapings revealed positive for Notoedres cati mite. Treatment with two doses of Ivermectin at the rate of 0.2 mg/kg body weight given by subcutaneous route biweekly for a month along with supportive therapy resulted in major improvement in the condition.